2007
DOI: 10.1089/neu.2007.3790
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Brain Injury in the Immature Rat: Evidence for an Age-at-Injury Effect on Cognitive Function and Histopathologic Damage

Abstract: Diffuse axonal injury is a significant component of the pathology of moderate-severe pediatric traumatic brain injury in children less than 4 years of age, and is associated with poor cognitive outcome. However, cognitive deficits or gross histopathologic abnormalities are typically not observed following moderate-severe diffuse brain injury in the immature (17-day-old) rat. In order to test whether the age of the immature animal may influence post-traumatic outcome, non-contusive brain trauma was induced in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 37 publications
(47 reference statements)
4
53
0
Order By: Relevance
“…The "optimal" age window appears to vary in different species. A critical developmental period with optimal postinsult recovery at around P30 has been observed in cats (Villablanca et al 1998) and at around P17 day in rats (Fineman et al 2000;Raghupathi and Huh 2007). Similarly in our study, a critical time window of in vitro development was found at around 8 DIV, during which hippocampal slice cultures were less vulnerable to injury responding with reduced deficits in the maximal evoked response and excitability.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The "optimal" age window appears to vary in different species. A critical developmental period with optimal postinsult recovery at around P30 has been observed in cats (Villablanca et al 1998) and at around P17 day in rats (Fineman et al 2000;Raghupathi and Huh 2007). Similarly in our study, a critical time window of in vitro development was found at around 8 DIV, during which hippocampal slice cultures were less vulnerable to injury responding with reduced deficits in the maximal evoked response and excitability.…”
Section: Discussionsupporting
confidence: 87%
“…On one hand, as reviewed by Prins and Hovda (2003), a critical developmental window may exist during the period of greatest neuronal plasticity and therefore potential recovery, which could alleviate posttraumatic degeneration of neural circuits and restore hippocampal organization and development. Consistent with the in vivo findings identifying a critical developmental period with maximal neuronal plasticity and optimal postinsult recovery at P17 (Fineman et al 2000;Raghupathi and Huh 2007), the window of greatest intrinsic neuronal plasticity is expected during the period of postnatal 15-24 days; thus 8 DIV for the cultures which were harvested from P9-to 10-day rat pups might be expected to be within the period of greatest intrinsic neuronal plasticity as well. On the other hand, taking into account the external effect of dissection and in vitro culture, the degeneration due to dissection may be complete by 8 DIV, as dissectioninduced, degenerated neuronal cells were rarely seen after 6 DIV in other studies (Kiernan and Pettit 1971).…”
Section: Discussionsupporting
confidence: 78%
“…Moderate and severe TBI in P11-P21 rodents has been shown to cause axonal degeneration detectable up to two weeks post-injury (Adelson et al, 2001;Raghupathi et al, 2002;Tong et al, 2002;Huh et al, 2007;Raghupathi and Huh, 2007). However, the onset and early progression of axonal injury in white matter tracts in response to brain injury has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Axonal injury has been described in the subcortical white matter following brain trauma in P11-21 rodents (Adelson et al, 2001;Tong et al, 2002;Huh et al, 2007;Raghupathi and Huh, 2007). However, no systematic data are available characterizing axonal degeneration in infant mice following TBI and its relationship to neuronal cell death.…”
Section: Introductionmentioning
confidence: 99%
“…9,17,40,41 In particular, Ibrahim and colleagues used the same RNR injury model but with rotations in the axial plane, and found that when five-day-old and four-week-old piglets experienced comparable mass-scaled angular accelerations the five-day-olds sustained significantly more TAI than the four-week-old piglets at the 6 h post-injury time point. 17 Although our dataset exhibited significantly higher TAI in five-day-olds overall ( p = 0.016), this did not reach significance at the 3-8 h time point and is somewhat confounded by the overall lower scaled angular velocities in the four-week-old age group.…”
Section: Figmentioning
confidence: 99%